Detection and identification of gonococcal L-Forms using a direct immunofluorescence test. Issue 3 (June 1977) - Waitkins, S A; Geary, I
Abstract : A fluorescent antibody test was used to identify L-Forms of N. gonorrhoeae induced in vitro. It was possible to differentiate the Large Bodies of the L-Forms from parent gonococci and the fluorescent reaction remained specific in the presence of tissue culture cells. A possible method to identify L-Forms of gonococci from patients presenting with postgonococcal urethritis is described.